2000
DOI: 10.1016/s0378-1097(00)00369-4
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde metabolism by wine lactic acid bacteria

Abstract: Acetaldehyde is a volatile flavor compound present in many fermented foods and is important in the production of red and white wines. Nine strains of the genera Lactobacillus and Oenococcus were able to metabolize acetaldehyde in a resting cell system, whereas two Pediococcus strains were not. Acetic acid and ethanol were produced from its degradation. A Lactobacillus and an Oenococcus were able to degrade SO 2 -bound acetaldehyde, as well. A coincubation of resting cells of Saccharomyces bayanus Premie ©re Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 12 publications
8
57
0
Order By: Relevance
“…However, no data quantifying acetaldehyde production among Saccharomyces and nonSaccharomyces wine yeast under comparable and easily reproducible conditions are available. Resting cell suspensions in a winemaking buffer system have been used in the past to study the metabolism of wine yeast and lactic acid bacteria providing results similar to fermentations in must, but in a fraction of the time required [22,28]. After standardized pre-growth of the yeast and adjustment of the biomass using a rapid method [19], resting cell incubations Yield coefficients were calculated as average amounts of acetaldehyde produced per glucose degraded during the initial acetaldehyde production phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no data quantifying acetaldehyde production among Saccharomyces and nonSaccharomyces wine yeast under comparable and easily reproducible conditions are available. Resting cell suspensions in a winemaking buffer system have been used in the past to study the metabolism of wine yeast and lactic acid bacteria providing results similar to fermentations in must, but in a fraction of the time required [22,28]. After standardized pre-growth of the yeast and adjustment of the biomass using a rapid method [19], resting cell incubations Yield coefficients were calculated as average amounts of acetaldehyde produced per glucose degraded during the initial acetaldehyde production phase.…”
Section: Discussionmentioning
confidence: 99%
“…Resting cell experiments were performed according to Osborne et al [28] with modifications. The glass vials containing yeast suspensions were placed in a water bath and stirred with Teflon-coated stir bars (4 9 1 mm) at 800 rpm using a submersible magnetic stirrer (2mag-USA, Daytona Beach, FL, USA).…”
Section: Resting Cell Experimentsmentioning
confidence: 99%
“…A signiWcant increase in the concentration of several esters produced by bacterial metabolism has been reported [11,39], whereas other studies reported reduced ester concentrations [24]. The catabolism of acetaldehyde by wine LAB was reported by Osborne et al [48]. This illustrates the potential of LAB to metabolise aldehydes [35] and, consequently, reduce the associated herbaceous aroma; reports on these changes during MLF are few, however.…”
Section: Introductionmentioning
confidence: 94%
“…The malolactic activity and biomass of L. brevis were inhibited when the ethanol concentration was increased over 110 g l -1 . O. oeni can grow through degradation from malic acid to lactic acid or acetic acid [40,41], chemical reduction from acetaldehyde to ethanol [17,27], and consumption of residual carbohydrates from the primary alcoholic fermentation. The malolactic activity and specific malolactic activity of L. brevis were drastically reduced at the alcohol concentration above 110 g l -1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all citric acid is metabolized into acetic acid and C 4 compounds, resulting in accumulation of diacetyl, acetoin, and acetic acid in wine. Usually more acetic acid is produced from the given amounts of citric acid during the MLF [3,16,32,24,26,27,18].…”
Section: Introductionmentioning
confidence: 99%